INVESTIGATION OF THE TRANSPORTATION SYSTEM AND TRANSPORTATION INFRASTRUCTURE OF TURKEY - Turan, Eda; Sahin, Bahri (YILDIZ TECHNICAL UNIV, 2014)
The mostly utilized transportation mode in cargo and passenger transportation is highway transportation in Turkey. The ratio of maritime transportation which is used mostly especially in international trade is seen as very low in inland transportation. Highway transportation enables the goods carried from origin to destination directly in a fast way. However, time of haul is longer in maritime transportation compared to highway transportation. Therefore, this mode can be an alternative for shipping of cargoes that do not need fast lead time. In this study, the current infrastructure of Turkey in highway, railway and maritime transportation has been investigated and compared subject to years.
Keywords: Transportation; highway; railway; maritime; Engineering